Bone Morphogenetic Protein 6 Polymorphisms are Associated With Systemic Lupus Erythematosus Susceptibility in the Korean Population - Ji-su MO; Soo-cheon CHAE (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate whether bone morphogenetic protein 6 (BMP6) single-nucleotide polymorphism (SNP) is associated with susceptibility to systematic lupus erythematosus (SLE). Patients and methods: We analyzed the genotype and allele frequencies of BMP6 SNPs using genomic deoxyribonucleic acid isolated from 119 SLE patients (9 males, 110 females; mean age 36.4 years; range 19 to 59 years) and 509 healthy controls (323 males, 186 females; mean age 42.1 years; range 19 to 61 years). Genomic deoxyribonucleic acid was extracted from peripheral blood leukocytes using a standard phenol-chloroform method or by using a genomic deoxyribonucleic acid extraction kit. Erythrocyte sedimentation rate, C-reactive protein, and antinuclear antibody levels of SLE patients were recorded. Results: Our results showed that the genotype frequencies of rs17557 and rs9505273 for BMP6 in SLE patients significantly differed from those of the control group (p=0.01 and p=0.04, respectively). The genotype frequencies of the rs17557 and rs9505273 for BMP6 in female SLE patients were also significantly different from those in female healthy controls (p=0.04 and p=0.03, respectively). We also revealed that the distribution of the main haplotypes of BMP6 SNPs in SLE patients was significantly different from their distribution in healthy controls. Conclusion: These results suggested that SNPs in BMP6 might be associated with susceptibility to SLE and that haplotypes of BMP6 polymorphisms might represent useful genetic markers for SLE.